Organizational citizenship behavior: understanding interaction effects of psychological ownership and agency systems - Ben Wilhelm; Nastaran Simarasl; Frederik J. Riar; Franz W. Kellermanns (Review of Managerial Science, 2022)
Organizational citizenship behavior is a highly sought-after outcome. We integrate insight from the psychological ownership perspective and agency theory to examine how the juxtaposition of informal psychological mechanisms (i.e., ownership feelings toward an organization) and formal and informal governance mechanisms (i.e., employee share ownership, agency monitoring, and peer monitoring) influences employees' organizational citizenship behaviors. Our empirical results show that psychological ownership has a positive effect on organizational citizenship behavior. Contrary to the common belief that informal and formal mechanisms complement each other, we find that the positive influence of psychological ownership on organizational citizenship behavior is more pronounced when employee share ownership and agency monitoring is low compared to high. Implications for theory and future research are discussed.
Keywords: L2; L7; M1; 650; Psychological ownership; Organizational citizenship behavior; Agency monitoring; Peer monitoring; Employee share ownership; Agency theory